The Oxford handbook of meaningful work - Yeoman, Ruth, 1964-; Bailey, Catherine (Catherine Truss); Madden, Adrian; Thompson, Marc, 1962- (Oxford : Oxford University Press, 2019)
This handbook examines the concept, practices, and effects of meaningful work in organisations and beyond. Taking an interdisciplinary approach, it reflects diverse scholarly contributions from philosophy, political theory, psychology, sociology, organisational studies, and economics.
The Moral Conditions of Work / Joanna Cuilla -- 'Belonging' and Its Relationship to the Experience of Meaningful Work / t
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 5, 2019).
Keywords: Work -- Psychological aspects; Psychology, Industrial; Work environment; Business ethics; Organizational behavior